Evaluation of the Tectonic Boundaries Using Potential Data at Tikrit-Kirkuk Area, North - Central Iraq - AL-Banna, Ahmed S.; Atwan, Dheyaa Sadoon (Iraqi Journal of Science, 2019)
The gravity and magnetic data of Tikrit-Kirkuk area in central Iraq were considered to study the tectonic situation in the area. The residual anomalies were separated from regional using space windows method with space of about 24, 12 and 10km to delineate the source level of the residual anomalies. The Total Horizontal Derivative (THD) is used to identify the fault trends in the basement and sedimentary rocks depending upon gravity and magnetic data. The identified faults in the study area show (NW-SE), less common (NE-SW) and rare (N-S) trends. Some of these faults extending from the basement to the upper most layer of the sedimentary rocks. It was found that the depth of some gravity and magnetic source range 12-13Km, which confirm the basement depth obtained by C.G.G. 1974. While the depth of shallow gravity source of about 4Km, this depth of the shallow source may be lay with sedimentary cover in Triassic age. A comparison of the residual gravity and magnetic anomalies of the relatively shallow depths showed a general coincidence. The obtained tectonic boundaries divided the study area to many blocks. The tectonic boundaries in general control the river running in the area, at the same time the longitudinal faults control the main oil fields in the study area.